Two-level cache based streaming media scheduling algorithm for mobile network - LIAO Jian-xin; YANG Bo; ZHU Xiao-min; WANG Chun (Tongxin xuebao)
A novel caching system architecture for mobile streaming was proposed,which was named 2CMSA（two-level cache mobile streaming architecture）.In this system,limitations for mobile streaming system such as small memory size in mobile terminal and low bandwidth in wireless access network were avoided.According to the 2CMSA,a scheduling algorithm of 2CMSS（two-level cache based mobile streaming scheduling） was designed;mathematical models were also achieved to analyze the performance of this scheduling algorithm.Simulation experiment proves that,comparing to the original mobile streaming system,by using the new two-level cache architecture and cache based scheduling algorithm,the network transmission cost and the client startup delay of the mobile streaming services can be decreased effectively.